Flop dead gorgeous - Rosenfelt, David (Farmington Hills, MI Thorndike Press, a part of Gale, a Cengage Company, 2023)
"Retired lawyer Andy Carpenter remembers every dog that's come through the Tara Foundation's doors, but the most well-known alum may be Mamie. Adopted by famous actress Jenny Nichols--Andy's high school girlfriend--the miniature French poodle is practically a starlet in her own right. Andy and his wife, Laurie, have dinner with Jenny while she's in town filming her next big hit. But the next morning Jenny's costar is found dead. Jenny is arrested for the murder and finds herself in need of Andy's legal services. While Mamie becomes reacquainted with Andy's golden retriever, Andy digs into the lives of the rich and famous"--
113358
Keywords: Carpenter, Andy -- (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; Trials (Murder) -- Fiction; Dogs -- Fiction; Dog rescue -- Fiction; Actresses -- Fiction; Large type books; New Jersey -- Fiction; Large type books; Detective and mystery fiction; Fiction; Cozy mysteries; Animal fiction; Novels